Effects of chromosomal heteromorphisms on reproductive health - Mehmet Caner Özer; Ayşegül Karahanoğlu; Zerrin Çelik (Journal of Comprehensive Surgery, 2026)
Chromosomal heteromorphisms (CHs) are structural chromosomal variants that are generally considered benign but have increasingly been investigated in relation to reproductive disorders. To review the current literature regarding the potential impact of CHs on reproductive health, including infertility, recurrent pregnancy loss, spermatogenesis, oogenesis, and assisted reproductive technologies. A narrative review of published studies evaluating the prevalence, biological mechanisms, and reproductive implications of CHs was conducted. Although CHs are traditionally regarded as normal cytogenetic variants, several studies have reported increased frequencies among individuals with infertility, recurrent pregnancy loss, and abnormal reproductive outcomes. Proposed mechanisms include alterations in meiotic chromosome pairing, chromatin condensation, gene regulation, and genome stability. However, findings remain inconsistent across studies. Current evidence suggests a possible association between CHs and adverse reproductive outcomes; however, a definitive causal relationship has not been established. Further prospective studies are required to clarify their clinical significance.